Scale-dependent effects of conspecific flower availability on pollination quantity and quality in an invasive shrub - Cavallero, Laura; Morales, Carolina Laura; Montero Castaño, Ana; Gowda, Juan H.; Aizen, Marcelo Adrian (Springer, 2022)
Pollen limitation can strongly influence reproduction of pollinator-dependent plants. Flower abundance can affect pollination ‘quantity’ and ‘quality’ due to its influence on pollen availability and foraging patterns of pollinators, ultimately impacting on seed production. We complemented individual-based measurements with landscape-level metrics to assess the influence of conspecific flower availability at different spatial scales on the quantity and quality components of pollination, and their impact on seed production in the invasive shrub Cytisus scoparius. In 2013–2014, we sampled 40 C. scoparius populations in Nahuel Huapi National Park, Patagonia (Argentina). In each population, we estimated the proportion of tripped flowers, fruit- and seed-set in five randomly selected individuals. The proportion of tripped flowers and the proportion of them setting fruit were used as proxies of pollination quantity and quality, respectively. Conspecific flower availability at distinct spatial scales (5–1000 m) was estimated as the area covered by flowering C. scoparius from color aerial photographs. Flower availability influenced seed output due to contrasting scale-dependent effects on pollination quantity and quality. Increasing flower availability at the landscape-scale reduced pollination quantity, whereas at the neighborhood-scale it increased pollination quality. The overall positive effect of flower availability on seed output at the neighborhood scale was slightly higher than the overall negative effect at the landscape scale. Moreover, pollination quality had a higher positive effect on seed output than pollination quantity. Our results demonstrate that pollination quality may severely limit plant reproduction. Pollination quality limitation can act independently of pollination quantity limitation because these factors operate at different spatial scales.